2008
DOI: 10.1021/jp7106999
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Catalyzed Clock Reaction

Abstract: Bulk Cu2O or cuprite is the only stable copper(I) compound present in plentiful amount in earth's crust. It is a challenging job to take bulk Cu2O to a nanoregime and to stabilize it in solution. No wonder that Cu2O in its nanoregime would act as a photocatalyst. We report a new synthetic protocol for the first time to obtain monodispersed, stable, exclusively cubic Cu2O nanoparticles in surfactant-free condition and its catalytic action for methylene blue (MB)−hydrazine reaction in aqueous medium. The blue co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…Studies by Pande et al [50] have shown that 15-nm Cu 2 O nanoparticles are able to reduce the activation energy by approximately 71 kJ mol −1 and hence, increase the reaction rate by 2.4 × 10 7 -fold. The reaction rate constant, k app , can be derived from the Arrhenius equation (Equation (7)).…”
Section: Activation Energymentioning
confidence: 99%
“…Studies by Pande et al [50] have shown that 15-nm Cu 2 O nanoparticles are able to reduce the activation energy by approximately 71 kJ mol −1 and hence, increase the reaction rate by 2.4 × 10 7 -fold. The reaction rate constant, k app , can be derived from the Arrhenius equation (Equation (7)).…”
Section: Activation Energymentioning
confidence: 99%
“…This is because the major oxidation states of Cu are Cu 4 O 3 , Cu 2 O, and CuO, 11 while the Cu 2+ state is considered to be more stable than the Cu + state. 12 The syntheses reported for the production of Cu 2 O are the hydrothermal, 13 polyol, [14][15][16] or glucose-reduction methods, 4 where the oxidation states of Cu are controlled with multiple steps to adjust the pH of the solvent, 16 the amount of reducing agent, 4,17 and the reduction rate. 12 In this report, we focus on layered silicon compounds (CaSi 2 and its derivative layered siloxene).…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2 O is also an effective photocatalyst able to decompose water into H 2 and O 2 under visible light [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%